In silico comparative analysis of LEA (Late Embryogenesis Abundant) proteins in Brachypodium distachyon L. - (:unkn) unknown (SOUTHERN CROSS PUBL, 2013)
The Late Embryogenesis Abundant (LEA) proteins in plants are basically related with water deficiency. Recent studies showed that LEA proteins might be molecular chaperones regulating many physiological functions. In this study, LEA proteins were analyzed in model grass Brachypodium distachyon L. The data represented here may help to further analyze the FA genes in model grass Brachypodium in order to understand their functions especially under conditions of water deficiency and/or other physiological mechanisms. By using the Pfam database, proteins containing at least one LEA conserved repeat (LEA2, LEA3, LEA4, LEAS, and LEA6) were classified as LEA family members. According to these results, 36 LEA proteins were identified in B. distachyon. LEA2 repeat was found as the dominant protein among 28 members followed by LEA3 (5 members). Physicochemical analysis showed that pI values and GRAVY index ranged from 4.40 to 11.1 and 0.48 to -1.423, respectively. Many LEA proteins were considered as basic character (26 members, 72.2%), while 10 proteins (27.8%) were in acidic form. Moreover, GRAVY index revealed that 19 of the 36 sequences were considered hydrophobic (52.8%) while others were hydrophilic (47.2%). Comparative phylogenetic analysis revealed that BdLEA proteins fall into eight subgroups. They were basically divided into two main groups. Chromosomal distribution of LEA genes was determined and segmental and tandem duplications were found in eight genes which may cause expansions of LEA genes through the Brachypodium genome. These results can be helpful for the further functional analysis of LEA proteins in Brachypodium.
Keywords: Brachypodium distachyon; LEA proteins; in silico analysis; phylogenetics; ARABIDOPSIS-THALIANA; GENE-EXPRESSION; GENOME; DUPLICATION; EVOLUTION; SEQUENCE; STRESS; COTTON; POPULATIONS; DIVERGENCE